Protective effect of neurofilament heavy gene overexpression in motor neuron disease induced by mutant superoxide dismutase - Couillard-Després, Sébastien (The National Academy of Sciences, 1998)
To investigate the role of neurofilaments in motor neuron disease caused by superoxide dismutase (SOD1) mutations, transgenic mice expressing a amyotrophic lateral sclerosis-linked SOD1 mutant (SOD1(G37R)) were mated with transgenic mice expressing human neurofilament heavy (NF-H) subunits. Unexpectedly, expression of human NF-H transgenes increased by up to 65%, the mean lifespan of SOD1(G37R) mice. Microscopic examination corroborated the protective effect of NF-H protein against SOD1 toxicity. Although massive neurodegeneration occurred in 1-yr-old mice expressing SOD1(G37R) alone, spinal root axons and motor neurons were remarkably spared in doubly SOD1(G37R);NF-H-transgenic littermates.